Holy shit : a brief history of swearing - Mohr, Melissa (Oxford ; New York : Oxford University Press, 2013)
"Holy Sh*t tells the story of two kinds of swearing--obscenities and oaths--from ancient Rome and the Bible to today. With humor and insight, Melissa Mohr takes readers on a journey to discover how "swearing" has come to include both testifying with your hand on the Bible and calling someone a *#$&!* when they cut you off on the highway. She explores obscenities in ancient Rome--which were remarkably similar to our own--and unearths the history of religious oaths in the Middle Ages, when swearing (or not swearing) an oath was often a matter of life and death. Holy Sh*t also explains the advancement of civility and corresponding censorship of language in the 18th century, considers the rise of racial slurs after World War II, examines the physiological effects of swearing (increased heart rate and greater pain tolerance), and answers a question that preoccupies the FCC, the US Senate, and anyone who has recently overheard little kids at a playground: are we swearing more now than people did in the past?"--Amazon.
To speak with Roman plainness : ancient Rome -- On Earth as it is in Heaven : the Bible -- Swearing God to pieces : the Middle Ages -- The rise of obscenity : the Renaissance -- The Age of Euphemism : the eighteenth and nineteenth centuries -- "Fuck 'em all" : swearing in the twentieth century and beyond.
Includes bibliographical references (p. 259-306).
Keywords: Swearing -- History; English language -- Obscene words -- History; English language -- Slang -- History; English language -- Social aspects -- History; English language -- History; Englisch; Fluch; Schimpfwort